Estimation of Drivers of Public Education Expenditure : Baumol's Effect Revisited - Nose, Manabu (IMF Working Papers; Working Paper, 2015)
This paper analyzes drivers of rising per-pupil public education spending, including Baumol's 'cost disease' effect. Higher wages paid to teachers contributed significantly to the increase in per-pupil spending over the past decades. Empirical analyses using a large dataset of advanced and developing economies show that the contribution of Baumol's effect was much smaller than impled by theory. Rather, the spending inccrease reflects rising wage premiums paid for teachers in excess of market wages, especially in middle-income countries. The strong wage premium effect suggests that institutional characteristics that govern teachers' wage setting are key determinants of education expenditure.